Anthelmintic and Drug Resistance in Ruminants - Garedaghi, Yagoob (Research Journal in Medical and Health Sciences, 2023)
The chemical compounds include various groups such as Benzimidazoles, Imidazothiazoles, Tetrahydropyrimidines, Salicylanides, Piperazines, Ivermectins, etc. These drugs should be used properly to get the desired results, worms be controlled and drug resistance against worms is reduced to a minimum.